Thermoelectric transport and microstructure of optimized Mg2Si0.8Sn0.2. Issue 40 (3rd August 2015) - de Boor, J.; Gupta, S.; Kolb, H.; Dasgupta, T.; Müller, E.
Abstract : We have optimized the thermoelectric material Mg2 Si0.8 Sn0.2 and analyzed the electronic transport employing a single parabolic band model. Abstract : Solid solutions of magnesium silicide and magnesium stannide exhibit excellent thermoelectric properties due to favorable electronic band structures and reduced thermal conductivity compared to the binary compounds. We have optimized the composition Mg2 Si0.8 Sn0.2 by Sb doping and obtained a thermoelectric figure of merit close to unity. The material comprises of several phases and exhibits intrinsic nanostructuring. Nevertheless, the main features of electronic transport can be understood within the framework of a single parabolic band model. Compared to Mg2 Si we observe a comparable power factor, a drastically reduced thermal conductivity and an increased effective mass.